The Impact Of Climate Change In Nigeria: Implications For Schooling - Goteng, Kak’mena Audu; Census, Hemba Emmanuel; Alikeju, Eyimoga Helen (Richtmann Publishing, 2012)
Although climate change is a global issue, likewise its impacts, but the biting effects are felt more by poor and developing countries especially those in Africa due to low level of infrastructural development, awareness and coping capacities. This can become worse if the educational systems of such countries experience serious setbacks as a result of the negative impacts of climate change. A lot of research has been carried out on the impact of climate change in Nigeria and the diverse ecological problems been faced today in the country have been linked to the ongoing climate change. However the impact of climate change on the access to quality education is yet to receive much attention. In this paper an overview of the impact of climate change as it affects schooling has been carried out with a view to spurring research on the subject matter.